Investigation of Landslide Vulnerability on Prambanan using Vertical Electrical Sounding - Pratomo, Awang Hendriato; Suharsono; Pratistho, Bambang; Prasetyo, Dessyanto Boedi; Pratama, Yudha Agung; Purnawan , Basuki (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this research to identify potential weak zone of landslides on Prambanan based on the geoelectric resistivity technique of Vertical Electric Sounding (VES) Schlumberger configuration. Data was collected as much as 7 point sounding ; each Spreading AB has a length of 80 meters. The location of landslide is near from resident house. Therefore evaluation using resistivity method is needed to identification vulnerability of landslide. There are 7 of data acquisition. Based on the inversion result, contrass resistivity zone identified as diferent border of layer. Based on 2D resistivity modeling results indicate that the slip field is at a depth of 1.02-7.8 meters in the form of weathered Tuffaceus Sandstone.